Optimizing scheduling performance through time slice management based on Max Min strategy in cloud system - Galolia, Nidhi P; Meniya, Arvind (International Journal of Computer Sciences and Engineering, 2019)
Cloud computing provides the architecture in which multiple virtual machines run in a single physical machine and delivering different types of services to users in pay per use bases. Due to limited resources of the physical machine, scheduling of available resources in an efficient manner is necessary for any cloud system and integration of such scheduling strategy in the system will reduce the overall execution time of the system and thus improve response time. In this paper novel scheduling algorithm is proposed IMT (Improved Makespan Time) which is built on the comprehensive study of existing scheduling algorithms such as max-min, min-min, SJF LJF Hybrid scheduling algorithm and many more. The algorithm is based on minimum execution time and maximum resource utilization strategy. Performance analysis of the proposed algorithm is carried out by comparing the execution time of the algorithm with other algorithms specified above using workflowsim simulation tool. Simulation results show that the proposed scheduling algorithm over performs existing algorithms in term of completion time.